Evaluation of commonly used tests to measure the effect of single-dose aspirin on mouse hemostasis. (October 2019) - Decouture, Benoit; Leuci, Alexandre; Dizier, Blandine; Belleville-Rolland, Tiphaine; Mansour, Alexandre; Martin, Fanny; Pidard, Dominique; Gaussem, Pascale; Bachelot-Loza, Christilla
Highlights: There are major discrepancies in preclinical studies of aspirin antiplatelet activity in murine models of bleeding and arterial thrombosis. Pre-clinical assays performed 30 min after oral administration of aspirin give more reproducible results compared to a 3 h delay. In contrast to tail bleeding cut, time to occlusion of FeCl3 -induced carotid arterial thrombosis is not an appropriate marker of aspirin efficacy on murine platelets. Abstract: Discrepancies in preclinical studies of aspirin (ASA) antiplatelet activity in mouse models of bleeding and arterial thrombosis led us to evaluate commonly reported methods in order to propose a procedure for reliably measuring the effects of single dose ASA on mouse hemostasis. FVB and C57Bl6 mice received 100 mg/kg of ASA or vehicle orally 30 min or 3 h prior to investigate either hemostasis using the tail bleeding assay or carotid thrombosis induced by FeCl3, or to blood sampling for isolated platelet aggregation and TXB2 generation. Expected inhibition of COX1 by ASA was ascertained by a strong decrease in TXB2 production, and its effect on platelet function and hemostasis, by decreased collagen-induced aggregation and increased bleeding time, respectively. Strikingly, we determined that anti-hemostatic effects of ASA were more predictable 30 min after administration than 3 h later. Conversely, ASA did not alter time to arterial occlusion of the carotid upon FeCl3 -induced thrombosis, suggesting ASA not to be used as reference inhibitor drug in this model of arterial thrombosis. Graphical abstract: Image, graphical abstract